Effective Removal of the Antibiotic Nafcillin from Water by Combining the Photoelectro-Fenton Process and Anaerobic Biological Digestion - Salazar-Gonzalez, R; Huilinir-Curio, C; Santander-Meyer, R; Vidal-Fuentes, J; Vidal-Fuentes, J (Elsevier B.V., 2018)
The elimination of the antibiotic Nafcillin (NAF), which is usually used in hospitals and veterinary clinics around the world, was assessed through a combination of three advanced electrochemical oxidation processes followed by anaerobic digestion process. In the first stage different electrochemical advanced oxidation processes (EAOPs) were used: electro-oxidation with hydrogen peroxide (EO-H2O2), electro-Fenton (EF) and Photo electro-Fenton (PEF). After PEF, almost complete and highly efficient degradation and elimination of NAF was achieved, with the concomitant elimination of the associated antimicrobial activity. The fast degradation rate produced by PEF is explained by the oxidative action of hydroxyl radicals (•OH) together with the direct UV photolysis of complexes formed between Fe3 + and some organic intermediates. Total removal of NAF occurs after 90 min of electrolysis by PEF, with the generation of organic intermediates that remain in solution. However, when this post PEF process solution was treated with an anaerobic biological process, the intermediates generated in the electrochemical degradation of NAF were completely eliminated after 24 h. The kinetic degradation of NAF as well as the identification/quantification of products and intermediates formed during the degradation of antibiotic, such as inorganic ions, carboxylic acids and aromatic compounds, were determined by chromatographic and photometric methods. Finally, an oxidation pathway is proposed for the complete conversion to CO2. © 2017